Da pisada do barro ao streaming: um estudo do samba de coco de Arcoverde-PE como indústria criativa para o desenvolvimento local. - Lourenço, Paula Santos (2024)
This dissertation seeks to understand how coconut samba groups from Arcoverde-PE can contribute to local development. For this, a case study of the Sesc PE Festival of Creative Economy: Na Pisada dos Cocos do Nordeste, a creative industry initiative led by coconut artists and held in the years 2021, 2022 and 2023 in the city. The project was created by the Social Service of Commerce (Sesc), with support from public and private entities. This work included a bibliographical review, in-depth interviews and direct and participatory observations of the artists and various actors in this process. Almeida (2011) and Lima (2018) were used as theoretical references for the popular demonstration of coconut; Canclini (1983) and Abib (2015) for popular cultures; Barbalho (2007), Calabre (2019), Canclini (1998) and Rubim (2007) for cultural policies; Bendassolli (2009), Howkins, (2013) and Leitão (2011 and 2023) for creative economy and Creative Industries; Serrão e Costa (2020) and Jara (2001) for local development; Tauk Santos (2015 and 2016) and Reis (2018) for local development and communication and Chiavenato and Sapiro (2004) for strategic planning. The study aims to answer the following research question: how does a festival based on popular culture contribute to local development? In this way, it is expected to identify the cultural, social and economic impacts generated by the project on the coconut groups and the municipality. As a product of intervention, a strategic plan was developed for the festival. The proposed solution can serve as inspiration for Sesc and cultural institutions to act in other contexts and places.